ASUHAN KEPERAWATAN DENGAN MASALAH STATUS KOPING KELUARGA PADA LANSIA ALZHEIMER: STUDI KASUS: Status Koping Keluarga - Beba, Nova Natalia; neng rifka, juliana (JURNAL KESEHATAN DAN TEKNOLOGI, 2024)
Alzheimer disease is a neurogenerative disease that attacks the brain and can affect a person's cognitive abilities. It can have an impact on family coping. Readiness to increase family coping is a pattern of adaptation of the family members themself in dealing with situations effectively and readiness to improve the health of the family and the client. Objective: to describe nursing care for client with family coping status problems to the elderly who has Alzheimer at Palu city, Central Sulawesi Province. Method: this research used a case study descriptive method, data were collected by using interviews and observations. The instruments used were assessment of the elderly, and Alzheimer's disease leaflet. Results: The problem was found, the client said that he did not know and understand his wife's Alzheimer disease, then based on this problem, there were 9 interventions given in accordance with Indonesian Nursing Intervention Standard (SIKI). Conclusion: After implementing the interventions for 5 consecutive days, the problem of readiness to increase family coping can be resolved. Therefore, it is hoped that the results of this case study can be applied to overcome the lack of family coping for Alzheimer's sufferers. Keywords: Alzheimer, Health Education, Readiness to increase family coping. Penyakit Alzheimer merupakan penyakit neurogeneratif yang menyerang otak dapat mempengaruhi kemampuan cara anggota keluarga dalam beradaptasi agar dapat menghadapi situasi dengan efektif dan siap meningkatkan kognitif keluarga dan individu. Tujuan : menggambarkan asuhan keperawatan pada klien dengan masalah status koping keluarga pada lansia Alzheimer di Kota Palu, Sulawesi Tengah. Metode : Penelitian dengan metode deskriptif studi kasus, dimana pengambilan data dilakukan dengan cara melakukan wawancara dan observasi. Tools yang digunakan adalah pengkajian lansia, dan leaflet penyakit Alzheimer. Hasil : ditemukan masalah klien mengatakan bahwa tidak mengetahui dan mengerti tentang penyakit Alzheimer yang diderita istrinya, kemudian berdasarkan masalah tersebut diberikan 9 intervensi sesuai dengan SIKI. Kesimpulan : Setelah dilakukan implementasi sesuai dengan intervensi selama 5 hari berturut-turut maka, masalah kesiapan peningkatan koping keluarga dapat teratasi. Oleh sebab itu diharapkan dengan hasil studi kasus ini dapat diterapkan untuk mengatasi kurangnya koping keluarga terhadap penderita Alzheimer Kata kunci: Alzheimer, Pendidikan Kesehatan, Kesiapan peningkatan koping keluarga